An extension of the linear delta expansion to superspace - Abdalla, M. C.B. [UNESP]; Helayël-Neto, J. A.; Nedel, Daniel L.; Senise, Carlos R. [UNESP] (American Physical Society (APS), 2008)
We introduce and discuss the method of linear delta expansion for the calculation of effective potentials in superspace, by adopting the improved version of the super-Feynman rules. Calculations are carried out up to two loops and an expression for the optimized Kähler potential in the Wess-Zumino model is worked out. © 2008 The American Physical Society.